CSR Practice and Asymmetry Information of Indonesian Public Listed Companies - Usman, Berto; Yennita, Yennita (Universitas Prasetiya Mulya, 2018)
Our study examines the relationship between Corporate Social Responsibility (CSR) practice and asymmetry information in the Indonesian Stock Exchange. We conjecture that these two concepts are negatively associated. To empirically test their association, we use the availability of CSR report, environmental score, and social score as the surrogate indicators of CSR practice. While, bid/ask spread (BAS) and price volatility (PV) are employed as the proxies of Asymmetry information. Using the quarterly data spans from the second quarter of 2012 to the fourth quarter of 2016, we collect as many as 39 companies that voluntarily disclosed their CSR-related information. To investigate the importance of CSR practice in the truncation of asymmetry information, we use the univariate analysis and multivariate analysis. We find that CSR practice is negatively associated with the asymmetry information. Our results remain consistently after we control for the firm-specific, year, and industry fixed-effect.